Does muscle size matter?: The relationship between muscle size and strength in children with cerebral palsy - Reid, S.; Pitcher, C.; Williams, Sian; Licari, M.; Valentine, J.; Shipman, P.; Elliott, Catherine (Informa Healthcare, 2015)
Purpose: To investigate the muscle size–strength relationship of the knee flexors and extensors in children with spastic cerebral palsy (CP) in relation to typically developing children (TD). Methods: Eighteen children with spastic Diplegia, Gross Motor Function Classification System I–III (mean 7 y 5 mo SD 1 y 7 mo) and 19 TD children (mean 7 y 6 mo SD 1 y 9 mo) participated. Muscle volume (MV) and anatomical cross-sectional area (aCSA) were assessed using MRI. Measures of peak torque (PT) and work of the knee flexors and extensors were assessed isometrically and isokinetically using a Biodex dynamometer, and normalised to bodymass (Bm). Results: Children with CP were weaker than their TD peers across all torque variables (p < 0.05). MV and aCSA of the knee flexors (MV: p = 0.002; aCSA: p = 0.000) and extensors (MV: p = 0.003; aCSA: p < 0.0001) were smaller in children with CP. The relationship between muscle size and strength in children with CP was weaker than the TD children. The strongest relationship was between MV and isometric PT/Bm for TD children (r = 0.77–0.84), and between MV and isokinetic work (r = 0.70–0.72) for children with CP. Conclusions: Children with CP have smaller, weaker muscles than their TD peers. However, muscle size may only partially explain their decreased torque capacity. MV appears to be a better predictor of muscle work in children with CP than aCSA. This is an important area of research particularly in regard to treatment(s) that target muscle and strength in children with CP.